(untitled) (Philologia, 2021)
Oliver Goldsmith (?1730-1774) is one of the most prominent representatives of English sentimentalism. Goldsmith’s best poem, The Deserted Village, was published in quarto, on May 26th 1770. In this poem Goldsmith describes depopulation of village in his country caused by the accumulation of wealth and the process of enclosing. There is a very good depiction of once idyllic and now deserted village. The portraits of the village preacher and the schoolmaster as well as the description of the village inn are artistically made.